Taohong Siwu Decoction enhances human bone marrow mesenchymal stem cells proliferation, migration and osteogenic differentiation via VEGF-FAK signaling in vitro. (10th May 2023) - Lu, Xiaolong; Li, Juan; Zhou, Biao; Lu, Xuedi; Li, Wei; Ouyang, Jian
Abstract: Ethnopharmacological relevance: Taohong Siwu Decoction (THSWD) is a conventional traditional Chinese prescription aiming at promoting blood circulation and alleviating blood stasis. It is widely prescribed in instances of ischemic strokes, cardiovascular diseases, osteoporosis and bone fracture. However, its molecular functions in bone formation remain uncharacterized. Aim of study: This study aims to explore the potential effects of THSWD treatment on human bone marrow mesenchymal stem cells (BMSCs) proliferation, osteogenic differentiation, and migration. Materials and methods: BMSCs undergo osteogenic, adipogenic, and chondrogenic differentiation to determine cell stemness. BMSCs were treated with low dose (200 μg/ml), medium dose (400 μg/ml) and high dose (600 μg/ml) THSWD. The cell viability was determined by CCK-8 assays, the osteogenic differentiation ability was determined by alizarin red staining and ALP staining, and cell migration was determined by wound healing and transwell assays. The effect of THSWD on the vascular endothelial growth factor (VEGF)/focal adhesion kinase (FAK) pathway was determined by immunoblotting. Results: THSWD time-dependently and dose-dependently promoted BMSC viability. Moreover, THSWD also promoted BMSC osteogenic differentiation and migration. As opposed to THSWD, VEGF receptor inhibitor Bevacizumab suppressed BMSC osteogenic differentiation and migration. In BMSCs that have been co-treated with THSWD and Bevacizumab, THSWD effects on BMSC functions were partially eliminated by Bevacizumab. Moreover, THSWD treatment boosted VEGF content in the supernatant and was conducive to the phosphorylation of FAK and Src, whereas Bevacizumab exerted opposite effects; similarly, Bevacizumab partially abolished THSWD effects on VEGF and FAK (Tyr397) and Src (Tyr418) phosphorylation. Conclusion: THSWD enhances the capacities of BMSCs to proliferate, differentiate, and migrate, possibly through VEGF and the FAK-Src, thereby improving fracture healing. Graphical abstract: Image 1 Highlights: THSWD promotes BMSCs viability, migration and osteogenic differentiation. THSWD promotes VEGF secretion and FAK phosphorylation. THSWD regulates BMSC functions through the VEGF-FAK signaling.